Placenta Derived Mesenchymal Stem Cells Hosted on RKKP Glass-Ceramic: A Tissue Engineering Strategy for Bone Regenerative Medicine Applications. (19th December 2016) - Ledda, Mario; Fosca, Marco; De Bonis, Angela; Curcio, Mariangela; Teghil, Roberto; Lolli, Maria Grazia; De Stefanis, Adriana; Marchese, Rodolfo; Rau, Julietta V.; Lisi, Antonella
Abstract : In tissue engineering protocols, the survival of transplanted stem cells is a limiting factor that could be overcome using a cell delivery matrix able to support cell proliferation and differentiation. With this aim, we studied the cell-friendly and biocompatible behavior of RKKP glass-ceramic coated Titanium (Ti) surface seeded with human amniotic mesenchymal stromal cells (hAMSCs) from placenta. The sol-gel synthesis procedure was used to prepare the RKKP glass-ceramic material, which was then deposited onto the Ti surface by Pulsed Laser Deposition method. The cell metabolic activity and proliferation rate, the cytoskeletal actin organization, and the cell cycle phase distribution in hAMSCs seeded on the RKKP coated Ti surface revealed no significant differences when compared to the cells grown on the treated plastic Petri dish. The health of of hAMSCs was also analysed studying the mRNA expressions of MSC key genes and the osteogenic commitment capability using qRT-PCR analysis which resulted in being unchanged in both substrates. In this study, the combination of the hAMSCs' properties together with the bioactive characteristics of RKKP glass-ceramics was investigated and the results obtained indicate its possible use as a new and interesting cell delivery system for bone tissue engineering and regenerative medicine applications.